Suicidal ideation and suicidal attempts in patients with obsessive-compulsive tic-related disorder vs obsessive-compulsive disorder: results of a multicenter Italian study. (6th August 2021) - Benatti, Beatrice; Ferrari, Silvia; Grancini, Benedetta; Girone, Nicolaja; Briguglio, Matteo; Marazziti, Donatella; Mucci, Federico; Dell'Osso, Liliana; Gambini, Orsola; Demartini, Benedetta; Tundo, Antonio; Necci, Roberta; et al.
Abstract: Background: Obsessive-compulsive disorder (OCD) and tic disorder (TD) represent highly disabling, chronic and often comorbid psychiatric conditions. While recent studies showed a high risk of suicide for patients with OCD, little is known about those patients with comorbid TD (OCTD). Aim of this study was to characterize suicidal behaviors among patients with OCD and OCTD. Methods: Three hundred and thirteen outpatients with OCD (n = 157) and OCTD (n = 156) were recruited from nine different psychiatric Italian departments and assessed using an ad-hoc developed questionnaire investigating, among other domains, suicide attempt (SA) and ideation (SI). The sample was divided into four subgroups: OCD with SA (OCD-SA), OCD without SA (OCD-noSA), OCTD with SA (OCTD-SA), and OCTD without SA (OCTD-noSA). Results: No differences between groups were found in terms of SI, while SA rates were significantly higher in patients with OCTD compared to patients with OCD. OCTD-SA group showed a significant male prevalence and higher unemployment rates compared to OCD-SA and OCD-noSA sample. Both OCTD-groups showed an earlier age of psychiatric comorbidity onset (other than TD) compared to the OCD-SA sample. Moreover, patients with OCTD-SA showed higher rates of other psychiatric comorbidities and positive psychiatric family history compared to the OCD-SA group and to the OCD-noSA groups. OCTD-SA and OCD-SA samples showed higher rates of antipsychotics therapies and treatment resistance compared to OCD-noSA groups. Conclusions: Patients with OCTD vs with OCD showed a significantly higher rate of SA with no differences in SI. In particular, OCTD-SA group showed different unfavorable epidemiological and clinical features which need to be confirmed in future prospective studies.